2014
DOI: 10.2500/ajra.2014.28.4109
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory Outcomes after Endoscopic Pituitary Surgery with Nasoseptal “Rescue” Flaps: Electrocautery versus Cold Knife

Abstract: Raising the rescue flap by cold knife could reduce the rate of hyposmia compared with using an electrocautery postoperatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
47
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 18 publications
5
47
0
2
Order By: Relevance
“…Three months after surgery, the average score in group II was above the preoperative score. Similar results were reported by Hong 27 and Sowerby. 28 Kim et al, 7 however, in their large series of 200 patients who underwent bilateral modified rescue flap, found a significantly worse olfactory score on both subjective and objective testing 6 months postoperatively.…”
Section: Discussionsupporting
confidence: 91%
“…Three months after surgery, the average score in group II was above the preoperative score. Similar results were reported by Hong 27 and Sowerby. 28 Kim et al, 7 however, in their large series of 200 patients who underwent bilateral modified rescue flap, found a significantly worse olfactory score on both subjective and objective testing 6 months postoperatively.…”
Section: Discussionsupporting
confidence: 91%
“…del techo de la fosa y en todos los pacientes hemos mantenido el cornete superior, el cual ha sido sindicado como una de las principales causas de las alteraciones olfatorias 17 . A su vez a diferencia de la técnica descrita por Hadad, quienes realizan el colgajo con electrobisturí, nuestra experiencia fue mejor al utilizar bisturí frio dado que con el monopolar y a pesar de utilizar punta fina, se generaron abundantes costras en la fosa nasal difíciles de manejar en el posoperatorio 13 . Para la medición del olfato existe varias técnicas, pero en nuestro servicio hemos decidido implementar una metodología sencilla, fácilmente aplicables y que presupuestariamente no sea onerosa 15 .…”
Section: Discussionunclassified
“…Durante la realización de la esfenoidotomía o el actuar sobre el septum posterior, este colgajo podría resultar lesionado. Así mismo, el instrumental con que se realiza este colgajo, ejemplo bisturí eléctrico aumentaría esta hiposmia 13 . Todo esto, conlleva posteriormente a un detrimento en la calidad de vida para el paciente 14 .…”
Section: Introductionunclassified
“…Oldfield et al, however, demonstrated the advantages of dissection of the histologic pseudocapsule surrounding pituitary adenomas, allowing microadenomas to ideally be resected in an en-bloc extracapsular fashion ( Figure 2B). 19 When feasible, en bloc resection reduces the likelihood of tumor remnants and increases biochemical remission for functional adenomas. 20 Rarely, in patients with Cushing's disease, a pituitary microadenoma may not be visible on MR imaging but the diagnosis confirmed by adrenocorticotropic hormone (ACTH)-dependent elevation of cortisol levels and…”
Section: Surgical Approach: Sellar Stagementioning
confidence: 99%